The Influence of Extending Concept Through Language Activities (ECOLA) Method in Students’ Reading Comprehension Ability in Bahasa Indonesia Subject Class V - Deka, N Reino Putri; Fatimah, Titim; Rohmah, Siti Khozanatu (Al-Aulad: Journal of Islamic Primary Education, 2024)
The purpose of this study was to measure the difference in the average increase in reading comprehension ability of fifth grade students in Indonesian language subjects who studied using the Extending Concept Through Language Activities (ECOLA) method with students who studied using the scientific approach. This study was a quasi-experimental study with the Nonequivalent Pretest-Posttest Control Group Design. The sample of this study was students of grades V-A and V-B of Madrasah Ibtidaiyah Al-Misbah, Bandung City. The data collection technique used was a reading comprehension ability test. The data analysis technique used an independent t-test with a significance level of 0.05. The results showed that students' reading comprehension ability before and after applying the ECOLA method increased by 79.90% with the interpretation category "effective". Students' reading comprehension ability before and after applying the scientific approach increased by 68.91% with the interpretation category "quite effective". The researcher concluded that there was a significant difference in the average increase in reading comprehension ability of fifth grade students who used the Extending Concept Through Language Activities (ECOLA) method and the scientific approach.